ANALISIS PENGARUH KOMPENSASI CEO DAN KARAKTERISTIK CEO TERHADAP AGRESIVITAS PAJAK DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - Desti Purwantoro; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of CEO compensation on tax aggressiveness, to determine the effect of CEO characteristics on tax aggressiveness, and to determine the effect of tax aggressiveness on firm value.This research is a quantitative descriptive study that serves to explain the description of the object of research through secondary data obtained from mining companies listed on the Indonesia Stock Exch1ange 2017-2019. Then the results of the data were analyzed using multiple linear regression analysis with the help of SPSS software.The results of this study indicate that the value of the T test in this study shows that CEO compensation has a sig value of 0.809 > 0.05 with a t_count value of -0.245 meaning that compensation has no significant negative effect on tax aggressiveness, CEO characteristics have a sig value. 0.838 > 0.05 with a t_count value of -0.208 meaning that the CEO characteristics have an insignificant negative effect on tax aggressiveness and tax aggressiveness has a sig value of 0.487 > 0.05 with a t_count value of -0.708 meaning that tax aggressiveness has no significant negative effect on firm value.